Efficacy and Feasibility of Programmed Death-1/Programmed Death Ligand-1 Blockade Therapy in Non-Small Cell Lung Cancer Patients With High Antinuclear Antibody Titers - Mouri, Atsuto; Kaira, Kyoichi; Yamaguchi, Ou; Hashimoto, Kosuke; Miura, Yu; Shiono, Ayako; Shinomiya, Shun; Akagami, Tomoe; Imai, Hisao; Kobayashi, Kunihiko; Kagamu, Hiroshi (Frontiers in Oncology, 2021)
Background: Immune checkpoint inhibitor (ICI) therapy has been described to markedly improve patient survival. However, reports describing the antitumor therapeutic efficacy and safety of ICIs in patients with autoantibodies are scarce. Methods: This study examined the efficacy and feasibility of ICIs in antinuclear antibody (ANA)-positive patients with non-small cell lung cancer (NSCLC). An ANA titer greater than 1:40 and 1:80 was defined as positive and high, respectively. Patients who were treated with ICIs at Saitama Medical University, International Medical Center between January 2016 and December 2018 were retrospectively reviewed. Results: One hundred and nineteen of the 266 patients (44.7%) who received nivolumab, pembrolizumab, and atezolizumab had positive ANA titers. Their median age was 69 (range, 39-84) years. The overall response rate of the ANA-positive patients was 35.9% (37/103), which was not less than that of the ANA-negative group. The median progression-free survival in the ANA-positive group was 6.3 months versus 4.3 months in the ANA-negative group (p=0.08). Twenty-seven ANA-positive patients (10.2%) had high ANA titers. However, ICI efficacy was not decreased in these patients. Regardless of the cutoff of ANA titers (1:40 or 1:80), the rate of patients who experienced adverse events were not significantly different between the two groups. Conclusion: The administration of ICIs to ANA-positive patients has clinical benefits. The prevalence of adverse events in the ANA-positive group was not higher than that in the ANA-negative group.